2019
DOI: 10.3390/jof5040117
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cryptic Species of Four Candida Complexes in a Culture Collection

Abstract: Candida spp. are one of the most common causes of fungal infections worldwide. The taxonomy of Candida is controversial and has undergone recent changes due to novel genetically related species. Therefore, some complexes of cryptic species have been proposed. In clinical settings, the correct identification of Candida species is relevant since some species are associated with high resistance to antifungal drugs and increased virulence. This study aimed to identify the species of four Candida complexes (C. albi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…NAC species were identified by PCR-RFLP assays using universal primers (Integrated DNA Technologies, USA) and restriction enzyme MspI as described by previous studies [24,25]. Total volume of PCR reactions was 30 μl containing 3 μl of DNA solution, 15 μl 2X Master Mix (Cat.# M7505, Promega, USA), 0.75 μl of each primer (0.25 μM) and distilled water up to 30 μl.…”
Section: Determination Of Nac Based On Pcr-rflp Techniquementioning
confidence: 99%
“…NAC species were identified by PCR-RFLP assays using universal primers (Integrated DNA Technologies, USA) and restriction enzyme MspI as described by previous studies [24,25]. Total volume of PCR reactions was 30 μl containing 3 μl of DNA solution, 15 μl 2X Master Mix (Cat.# M7505, Promega, USA), 0.75 μl of each primer (0.25 μM) and distilled water up to 30 μl.…”
Section: Determination Of Nac Based On Pcr-rflp Techniquementioning
confidence: 99%
“…Within the isolates classified in the albicans complex, 2.8% were C. dubliniensis , while C. africana was not found. Fontecha et al reported 5% of C. dubliniensis and 3% of C. africana among 66 yeasts isolated in the same hospital [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since C. dubliniensis was first identified in Ireland as the cause of oropharyngeal candidiasis in patients living with HIV, it has been identified in many other countries [ 19 , 28 , 57 - 61 ]. The pathogenesis and antifungal susceptibility of C. dubliniensis are not clearly defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is described that the methodologies traditionally used for identifying yeasts, such as conventional phenotypic tests (biochemical tests, chromogenic media), are not able to correctly identify the cryptic species of Candida spp. (Fontecha, et al, 2019). An increase in the number of infections caused by unusual Candida species has been described in recent years (Tsai, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%